2003
DOI: 10.1182/blood-2002-12-3826
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Notch ligand, Jagged-1, induces alloantigen-specific human regulatory T cells

Abstract: Graft-versus-host disease (GVHD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 39 publications
3
110
1
Order By: Relevance
“…32 In the current study, we quantified the mRNA expression of Notch1, Hes1, and Hey1 in DAPTcultured PBMCs. 34,35 It was shown that Treg-triggered Notch1 activation of the target cells by membrane-bound TGF-b and blockage of Notch1 signaling reversed the immune suppression function of Treg cells. 36 Further research also revealed that Treg cells preferentially expressed cell membrane Notch ligands and that blocking Notch signaling initiated by such ligands inhibited Treg cell suppressor function.…”
Section: Discussionmentioning
confidence: 99%
“…32 In the current study, we quantified the mRNA expression of Notch1, Hes1, and Hey1 in DAPTcultured PBMCs. 34,35 It was shown that Treg-triggered Notch1 activation of the target cells by membrane-bound TGF-b and blockage of Notch1 signaling reversed the immune suppression function of Treg cells. 36 Further research also revealed that Treg cells preferentially expressed cell membrane Notch ligands and that blocking Notch signaling initiated by such ligands inhibited Treg cell suppressor function.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were incubated at a 1:1 ratio in 96-well plates (1 Â 10 5 cells per well for each population) with 40 Gyirradiated stimulator cells. Proliferation was measured on day 5 by [ 3 H]thymidine incorporation (22). Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Notch has been described to be involved in these late antigen-dependent differentiation steps. Initial studies had reported the development of regulatory T cells in the mouse and human system by Jagged1-overexpressing APC [12][13][14] and the induction of IFN-c-secreting Th1 cells as the result of a Dll1/ Notch3 interaction [15]. Recently, Amsen et al [16] showed that APC generally use the Notch pathway to instruct Th cell differentiation.…”
Section: Introductionmentioning
confidence: 99%